Self‐reported gastrointestinal disorders among veterans with gulf war illness with and without posttraumatic stress disorder. Issue 5 (21st March 2023) - Malhotra, D.; Boyle, S. H.; Gifford, E. J.; Sullivan, B. A.; Nguyen Wenker, T. H.; ABS, Nono‐Djotsa; Ahmed, S. T.; Upchurch, J.; Vahey, J.; Stafford, C.; Efird, J. T.; Hunt, S. C.; et al.
Abstract: Background: Gulf War Illness (GWI) is a chronic, multi‐symptom disorder affecting 25%–32% of Gulf War veterans. Veterans with GWI disproportionately suffer from gastrointestinal (GI) disorders. Given the increasing evidence supporting a gut‐brain axis, we explore the relationship between post‐traumatic stress disorder (PTSD), GWI, and self‐reported GI disorders among GW veterans. Methods: Veterans from the Gulf War Era Cohort and Biorepository responded to a mail‐based survey ( N = 1058). They were stratified by GWI (Centers for Disease Control definition) and PTSD status. This yielded three groups: GWI−, GWI+/PTSD−, and GWI+/PTSD+. Multivariable logistic regression adjusting for demographic and military characteristics examined associations between GWI/PTSD groups and GI disorders. Results were expressed as adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). Key Results: The most frequently reported GI disorders were irritable bowel syndrome (IBS), gastroesophageal reflux disease (GERD), and colon polyps (CP). The GWI+/PTSD+ group had a higher odds of these disorders than the GWI+/PTSD− group (aORIBS = 3.12, 95% CI: 1.93–5.05; aORGERD = 2.04, 95% CI: 1.44–2.90; aORCP = 1.85, 95% CI: 1.23–2.80), which had a higher odds of these disorders than the GWI− group (aORIBS = 4.38, 95% CI: 1.55–12.36; aORGERD = 2.51 95% CI: 1.63–3.87; aORCP = 2.57, 95% CI: 1.53–4.32). Conclusions & Inferences: GW veterans with GWI and PTSD have significantly higher odds of specific self‐reported GI disorders than the other groups. Given the known bidirectional influences of the gut and brain, these veterans may benefit from a holistic healthcare approach that considers biopsychosocial contributors to the assessment and management of disease. Abstract : The most frequent self‐reported GI disorders in this cohort were IBS, GERD, and colon polyps. The GWI+/PTSD+ group had a higher likelihood of IBS, GERD, and colon polyps than the GWI+/PTSD− group, which had a higher likelihood of all three disorders than the GWI− group.